Effect of chemical treatments and coupling agents on the properties of unidirectional jute fiber reinforced polypropylene composite - Roy, Subashis Kumar; Khan, G. M. Arifuzzaman; Haque, M. Ahsanul; Alam, Md. Shamsul; Haque, Md. Islamul; Gafur, M. A. (Penerbit Universiti Kebangsaan Malaysia, 2017)
Due to different chemical nature of jute and polypropylene, their blended composite materials often show failures behavior when applied in load bearing purposes. The aim of the research is to improve the properties of unidirectional jute fiber (JF) reinforced polypropylene (PP) composite. Unidirectional fiber composite was produced by simple hot press molding method according to weight percentage of 30wt% filler (JF), 2wt% coupling agent (compatibilizer) degraded PP (DgPP) and maleated PP (MAPP) and 68 wt% matrix (PP). To improve the interfacial interactions between the fiber and PP, the fiber was chemically modified with 10w/v% NaOH, 6w/v% dicumylperoxide (DCPO), 0.05 w/v% K2Cr2O7 and 5 w/v% H2O2 solution. The water absorption, tensile and thermal properties of raw and surface treated fibers composites were compared in particular coupling agent. It has found that the fiber treatments and addition of coupling agents, composites showed better properties. Among the composites, 10 wt/v% NaOH treated jute reinforced PP composite by using MAPP compatibilizer was presented better water absorption and mechanical properties. The positive change of the treated fiber composites was also found in case of the thermal stability that investigated by the TG, DTA and DTG tests.